2012
DOI: 10.7162/s1809-97772012000300012
|View full text |Cite
|
Sign up to set email alerts
|

Remote hearing aid fitting: Tele-audiology in the context of Brazilian Public Policy

Abstract: Summary Introduction: Currently, the Brazilian government has certificated nearly 140 specialized centers in hearing aid fittings through the Brazilian National Health System (SUS). Remote fitting through the Internet can allow a broader and more efficient coverage with a higher likelihood of success for patients covered by the SUS, as they can receive fittings from their own homes instead of going to the few and distant specialized centers. Aim: To describe a case of remote fitting between 2 cities, with revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 45 publications
0
37
0
3
Order By: Relevance
“…Penteado et al 24 reported three successful cases of remote hearing aid fitting between a large urban academic center and a smaller healthcare center in a resource-limited region of Brazil. Although no objective outcomes or comparisons were provided, this report provides an explanation of the process and value of providing teleaudiology services and educating local audiologists within a rural region with a lack of hearing specialists.…”
Section: Resultsmentioning
confidence: 99%
“…Penteado et al 24 reported three successful cases of remote hearing aid fitting between a large urban academic center and a smaller healthcare center in a resource-limited region of Brazil. Although no objective outcomes or comparisons were provided, this report provides an explanation of the process and value of providing teleaudiology services and educating local audiologists within a rural region with a lack of hearing specialists.…”
Section: Resultsmentioning
confidence: 99%
“…In both studies, no differences between the two methods were found in the final cochlear implant parameters or in patient satisfaction. Other studies, such as those of Gladden and Beck (2015), Penteado et al (2012), and Kuzovkov et al (2014) have also confirmed the equivalence of hearing aid and cochlear implant outcomes when devices are fitted via tele-audiology or through conventional face-to-face clinical encounters.…”
Section: Sensory Managementmentioning
confidence: 75%
“…These video and audio files were large and might have congested the bandwidth, thereby slowing transmission of information from the host computer to the remote computer. However, in a related telehealth study, Penteado et al (2012) attributed the delay in THM to the distance between the host and remote sites and that the farther the distance the slower the speed of data transmission and vice versa. These authors also attributed the time lag in telehealth to the type of OS used by the computers.…”
Section: Discussionmentioning
confidence: 99%
“…The hybrid model combines both synchronous and asynchronous telehealth models (Krumm, 2010). Information and communication technologies as well as the advent of the internet have provided opportunities for serving communities with limited access to health care, and a number of such studies in audiology abound (Schmiedge, 1997;Givens et al, 2003;Ribera, 2005;Choi et al, 2007;Krumm et al, 2007;Ferrari and Bernardez-Braga, 2009;Ramos et al, 2009;Swanepoel et al, 2010;Penteado et al, 2012).…”
mentioning
confidence: 99%